Thermal conductivities and diffusivities of graphite-epoxy composites - Han, Lit S.; Boyes, William F.; Air Force Wright Aeronautical Laboratories; Air Force Flight Dynamics Laboratory (U.S.); Ohio State University. Department of Mechanical Engineering (Wright-Patterson Air Force Base, Ohio : Flight Dynamics Laboratory, Air Force Wright Aeronautical Laboratories, Air Force Systems Command, United States Air Force, 1983)
Transient heat conduction experiments were performed on graphite- epoxy composites with fibers oriented uni-directionally in the matrix. With the fiber axis arranged parallel or transverse to the 4 heat flow direction, effective thermal conductivities and diffusiveities in the three orthogonal directions were obtained. also determined in this work were the isotropic conductivity and diffusivity for the epoxy resin (Fibrite No. 934) as 0.136 BTU/ hr-F-ft. and 8.5. x 10 to the 7th power sec, respectively. A value of k=6.0 BTU/ hr-F-ft for carbon fobers (Hercules 3501-5A) in the axial direction was deduced. For the conductivity transverse to the fibers, a value of 2.4 BTU/hr-F-ft was obtained from the measured effective transverse conductivity values. The thermal capacities (pC) for the carbon fibers and resin used in this study were determined as 48.2 and 44.4 BTU/cu ft 3-F, respectively.
"Report for period January 1982 - December 1982."
"February 1983."
Includes bibliographic references (page 79).
Work performed by The Ohio State University, Department of Mechanical Engineering, Columbus, Ohio, for the United States Air Force under contract
Mode of access: Internet.
Keywords: Fibrous composites -- Thermal properties; Graphite composites -- Thermal properties; Epoxy compounds -- Thermal properties